EIF4A3-induced circular RNA ASAP1 promotes tumorigenesis and temozolomide resistance of glioblastoma via NRAS/MEK1/ERK1–2 signaling. Issue 4 (14th September 2020) - Wei, Yutian; Lu, Chenfei; Zhou, Peng; Zhao, Lin; Lyu, Xiao; Yin, Jianxing; Shi, ZhuMei; You, Yongping
Abstract: Background: Acquired chemoresistance is a major challenge in the clinical treatment of glioblastoma (GBM). Circular RNAs have been verified to play a role in tumor chemoresistance. However, the underlying mechanisms remain unclear. The aim of this study was to elucidate the potential role and molecular mechanism of circular (circ)RNA ADP-ribosylation factor GTPase activating proteins with Src homology 3 domain, ankyrin repeat and Pleckstrin homology domain 1 (circASAP1) in temozolomide (TMZ) resistance of GBM. Methods: We analyzed circRNA alterations in recurrent GBM tissues relative to primary GBM through RNA sequencing. Real-time quantitative reverse transcription PCR verified the expression of circASAP1 in tissues and cells. Knockdown and overexpressed plasmids were used to evaluate the effect of circASAP1 on GBM cell proliferation and TMZ-induced apoptosis. Mechanistically, fluorescent in situ hybridization, dual-luciferase reporter, and RNA immunoprecipitation assays were performed to confirm the regulatory network of circASAP1/miR-502-5p/neuroblastoma Ras (NRAS). An intracranial tumor model was used to verify our findings in vivo. Results: CircASAP1 expression was significantly upregulated in recurrent GBM tissues and TMZ-resistant cell lines. CircASAP1 overexpression enhanced GBM cell proliferation and TMZ resistance, which could be reduced by circASAP1 knockdown. Further experiments revealed that circASAP1 increased the expression of NRAS via sponging miR-502-5p. Moreover, circASAP1 depletion effectively restored the sensitivity of TMZ-resistant xenografts to TMZ treatment in vivo. Conclusions: Our data demonstrate that circASAP1 exerts regulatory functions in GBM and that competing endogenous (ce)RNA-mediated microRNA sequestration might be a potential therapeutic strategy for GBM treatment.